The use of English discourse markers across gender: A corpus-based study - Ratih, Elisa; Abidah, Khilda Husnia (LingTera, 2022)
The current study aims to investigate the kinds of discourse markers (DMs) used by Indonesian university students in their cause-and-effect essay writing with consideration of gender groups. Twenty-nine cause-and-effect essays composed by 10 male and 19 female university students were analyzed using the DM taxonomy adapted from Fraser's (1999) and Halliday and Hasan's (1976) studies. AntConc 3.5.7 was utilized to find out the types and the frequency of the discourse markers in a corpus-based data analysis. The analysis identified 191 DMs from the 29 cause-and-effect essays. The findings revealed that, in terms of DM variability, there were no notable differences between the use of DMs by the male and female students. However, the study also observed some excessive use of DMs and a general lack of consideration of punctuations following the DMs by some of the male students. Taken together, our findings suggest a degree of similarities between the use of DMs by the male and female students with some potential limitations shown by the male students. Implications for the teaching of discourse markers as well as recommendations for future research are discussed.